Alcohol consumption, multiple Lugol‐voiding lesions, and field cancerization - Chikatoshi Katada; Tetsuji Yokoyama; Tomonori Yano; Haruhisa Suzuki; Yasuaki Furue; Keiko Yamamoto; Hisashi Doyama; Tomoyuki Koike; Masashi Tamaoki; Noboru Kawata; Motohiro Hirao; Yoshiro Kawahara; et al. (DEN Open)
Abstract The development of multiple squamous cell carcinomas (SCC) in the upper aerodigestive tract, which includes the oral cavity, pharynx, larynx, and esophagus, is explained by field cancerization and is associated with alcohol consumption and cigarette smoking. We reviewed the association between alcohol consumption, multiple Lugol‐voiding lesions, and field cancerization, mainly based on the Japan Esophageal Cohort study. The Japan Esophageal Cohort study is a prospective cohort study that enrolled patients with esophageal SCC after endoscopic resection. Enrolled patients received surveillance by gastrointestinal endoscopy every 6 months and surveillance by an otolaryngologist every 12 months. The Japan Esophageal Cohort study showed that esophageal SCC and head and neck SCC that developed after endoscopic resection for esophageal SCC were associated with genetic polymorphisms related to alcohol metabolism. They were also associated with Lugol‐voiding lesions grade in the background esophageal mucosa, the score of the health risk appraisal model for predicting the risk of esophageal SCC, macrocytosis, and score on alcohol use disorders identification test. The standardized incidence ratio of head and neck SCC in patients with esophageal SCC after endoscopic resection was extremely high compared to the general population. Drinking and smoking cessation is strongly recommended to reduce the risk of metachronous esophageal SCC after treatment of esophageal SCC. Risk factors for field cancerization provide opportunities for early diagnosis and minimally invasive treatment. Lifestyle guidance of alcohol consumption and cigarette smoking for esophageal precancerous conditions, which are endoscopically visualized as multiple Lugol‐voiding lesions, may play a pivotal role in decreasing the incidence and mortality of esophageal SCC.